Risk factors for malignancy in systemic sclerosis patients - Kasifoglu, T.; Bilge, S. Yasar; Yildiz, F.; Ozen, G.; Pehlivan, Y.; Yilmaz, N.; Onat, A. M. (Springer London Ltd, 2016)
Systemic sclerosis (SSc) is an autoimmune connective tissue disease with multisystem involvement. An increased incidence of cancer in SSc patients compared with the general population has been reported in several reports. Our aims in this study were to determine the most common malignancies and to investigate the possible risk factors for the development of malignancy in patients with SSc. Three hundred forty SSc patients from 13 centers were included to the study. Data of the patients were obtained by evaluating their medical records retrospectively. A total of 340 patients with SSc were evaluated. Twenty-five of the patients had 19 different types of malignancy. Bladder cancer was the most common type of cancer with four patients and was followed by breast cancer with three patients, and cervix cancer and ovarian cancer with two patients each. Other types of cancers such as squamous cell skin cancer, adenocancer with an unknown origin, multiple myeloma, chronic myeloid leukemia, papillary thyroid cancer, larynx cancer, non-small cell lung cancer, follicular type non-Hodgkin lymphoma (NHL), endometrium cancer, colon cancer, uterus cancer, neuroendocrine tumor, glioblastoma multiforme, and soft tissue sarcoma were diagnosed in one patient each. The only cancer type that showed an association with cyclophosphamide dose was bladder carcinoma. Other malignancies did not show a correlation with age, sex, smoking, type and duration of the disease, autoantibodies, organ involvement, and dose and duration of cyclophosphamide therapy. Cancer may develop in any organ in patients with SSc. Continuous screening of the patients during a follow-up period is necessary for the early detection of the tumor development.
Annual Meeting of Spondyloarthritis-Research-and-Treatment-Network (SPARTAN) -- JUL 25-26, 2015 -- Denver, CO
Keywords: Cyclophosphamide; Malignancy; Systemic sclerosis